Friends First? The Peer Network Origins of Adolescent Dating. (9th January 2015) - Kreager, Derek A.; Molloy, Lauren E.; Moody, James; Feinberg, Mark E.
Abstract : The proximity of dating partners in peer friendship networks has important implications for the diffusion of health‐risk behaviors and adolescent social development. We derive two competing hypotheses for the friendship–romance association. The first predicts that daters are proximally positioned in friendship networks prior to dating and that opposite‐gender friends are likely to transition to dating. The second predicts that dating typically crosses group boundaries and opposite‐gender friends are unlikely to later date. We test these hypotheses with longitudinal friendship data for 626 ninth‐grade PROSPER heterosexual dating couples. Results primarily support the second hypothesis: Romantic partners are unlikely to be friends in the previous year or share the same cohesive subgroup, and opposite‐gender friends are unlikely to transition to dating.